Permainan Puzzle Dalam Meningkatkan Perkembangan Kognitif Anak Usia Dini 5-6 Tahun - Sidiq, Adelia Miranti; Azizah Nurul Fadlillah (STAI Al-Amin Gersik Kediri Lombok Barat NTB, 2023)
Early childhood cognitive development becomes one of the factors in the development of children's abilities related to knowledge, understanding and psychological processes of children towards the surrounding environment. Playing puzzles is a form of play that can challenge children's creativity and memory. This game is used by teachers and parents as an alternative medium for stimulating early childhood cognitive development. The type of research used is a qualitative method with a literature review or literature review approach. This study aims to analyze puzzle games in improving the cognitive development of early childhood 5-6 years. Based on the results of the study conducted by the researchers, it was concluded that through puzzles children will learn to understand and process information, solve problems and know something. As for this study, the authors used a descriptive qualitative method, which is a formulation of the problem that guides research to explore or photograph social situations that will be examined thoroughly, broadly and in depth.